2021
DOI: 10.3390/plants10081750
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Young Pea and Barley Seedlings to Plasma-Activated Water

Abstract: This study demonstrates the indirect effects of non-thermal ambient air plasmas (NTP) on seed germination and plant growth. It investigates the effect of plasma-activated water (PAW) on 3-day-old seedlings of two important farm plants—barley and pea. Applying different types of PAW on pea seedlings exhibited stimulation of amylase activity and had no inhibition of seed germination, total protein concentration or protease activity. Moreover, PAW caused no or only moderate oxidative stress that was in most cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…As well as low- and high-voltage electrical discharge [ 40 , 41 ], pulsed magnetic field [ 42 ], and UV-A rays [ 43 ], CAP technology has shown many advantages in the agriculture sector [ 44 , 45 ]. Deferent plasma generation methods and setups have been presented and have also shown that plasma-treated solutions can be used along with CAP sources for “indirect” treatment [ 46 , 47 ]. The influence of plasma treatment on DNA damage, gene expression, enzymatic activity, morphological and chemical changes, germination, and resistance to stress is under research [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…As well as low- and high-voltage electrical discharge [ 40 , 41 ], pulsed magnetic field [ 42 ], and UV-A rays [ 43 ], CAP technology has shown many advantages in the agriculture sector [ 44 , 45 ]. Deferent plasma generation methods and setups have been presented and have also shown that plasma-treated solutions can be used along with CAP sources for “indirect” treatment [ 46 , 47 ]. The influence of plasma treatment on DNA damage, gene expression, enzymatic activity, morphological and chemical changes, germination, and resistance to stress is under research [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…These changes result from the effects of plasma activation [7,10,17]. The application of PAW in agriculture has arisen with various uses such as seed treatment [18][19][20][21], crop growth improvement [11,[22][23][24][25], and disease management [26][27][28]. In the plant growth process, the uptake of N 2 in the form of NO 3 − or NH 4 + is facilitated by the transport of specific proteins to the cell plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The application of NTP in agriculture includes both direct and indirect means of NTP treatment. A quantity of published data demonstrate mechanisms of direct interactions between plasma and plant material [17]. Indirect NTP treatments are used less often, it is usually the application of plasma-activated water (PAW) to the plant [18,19].…”
mentioning
confidence: 99%
“…The work of Kostolani et al [17] aimed to investigate the effect of PAW on threeday-old pea (Pisum sativum cv. Eso) and barley (Hordeum vulgare cv.…”
mentioning
confidence: 99%
See 1 more Smart Citation